The Impact of Compensation, Motivation, and Job Satisfaction on Employee Performance - Elprida Sidabutar; Tantri Yanuar Rahmat Syah; Rina Anindita (Journal of Multidisciplinary Academic, 2020)
Employee Performance is the main concern for every company, due to employee performance can be a benchmark in the success rate from a company. Therefore, employee performance is the new one of interesting topics to research. In this study aimed to examine the effect of compensation, motivation, and job satisfaction on employee performance. To achieve this goal, data were collected by online survey of 150 employees. The collected data were analyzed using SPSS and Structural Equation Modelling (SEM). The results of this research are indicating if compensation, motivation, and job satisfaction can improve employee performance. Therefore, this research has several important conclusions for company management, if with compensation, motivation and job satisfaction; the employee's performance will increase